State-of-the-art on the development of ultrasonic equipment and key problems of ultrasonic oil prudction technique for EOR in China. (February 2018) - Wang, Zhenjun; Gu, Simin
Abstract: As one of EOR techniques, ultrasonic oil production attracts more attention due to its simplicity, lower expenses, good applicability and no reservoir. In this paper, recent progress on ultrasonic oil recovery techniques in China is summarized in view of ultrasonic paraffin inhibiting and crude oil viscosity reduction, ultrasound-chemical combination treatment for the removal of plugs for near-well ultrasonic processing technology and ultrasound-chemical combination demulsification -dehydration. Especially, Recent inventions of ultrasonic oil production equipment for EOR in China are reviewed. The purpose of this paper is to provide reference for the broad applications of ultrasonic oil production for EOR techniques.